Branding and Digital Marketing Strategy to Increase the Potential of Janti Park Tourism Object Klaten Regency - Aziz, Riyan Abdul; Turmudi, Hadis; Widiati, Ina Sholihah; Lashwaty, Nina Dewi; Kurniawan, Twojar Shahirul; Daffa, Muhammad (Edumedia Solution, 2025)
The tourism sector is one sector that can have a major economic impact on every village community. One of the villages that uses the tourism sector to revive its village economy is Janti Village with one of its leading tourist attractions, Janti Park. The main challenge for the Janti Park tourist attraction is the branding and digital marketing process which is less than optimal, resulting in less than optimal number of visitors. The community service team solved the partner's problem in three main stages: the branding stage, the training stage, and the mentoring stage. The branding stage produces logos, print designs, and merchandise. The training stage partners gain expertise in photography, videography, promotional content creation, application of SEO techniques, and optimization of paid advertising. The mentoring stage produces content for each social media increasing to 32 content, the number of content views on Instagram increases above 3000 views, and the number of content views on TikTok increases above 5000 views.